Explaining Consumer Purchase Decisions Through Store Image, Store Atmosphere, And Word of Mouth: Evidence From A Batik Retailer in Bali - Dinda Ayu Suastini; Ni Wayan Eka Mitariani; I Made Surya Prayoga (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Store image, store atmosphere, and word of mouth are key factors that shape consumers’ perceptions, comfort, and confidence when making purchases. However, the inconsistent findings of previous studies regarding the influence of these three variables on purchasing decisions underscore the need for further research. This study aims to analyze the influence of store image, store atmosphere, and word of mouth on purchasing decisions among consumers of the Sari Amerta Batik Collection in Bali. The research sample consisted of 112 respondents who are consumers of the Sari Amerta Batik Collection in Bali. Data collection was conducted through the distribution of a questionnaire measured using a Likert scale with a range of values from 1 to 5. The data analysis technique used in this study is multiple linear regression analysis. The results indicate that store image has a positive and significant effect on purchase decisions among consumers of the Sari Amerta Batik Collection in Bali. Store atmosphere also has a positive and significant effect on purchase decisions among consumers of the Sari Amerta Batik Collection in Bali. Word of mouth has a positive and significant effect on purchase decisions among consumers of the Sari Amerta Batik Collection in Bali.